A Study on Hot Topics in Social Media of Tokyo 2020 Olympic Games - Chen, Hongbing (Technium Social Sciences Journal, 2022)
During the Tokyo 2020 Olympic Games, Sina Weibo, as a high-frequency platform, has a wide range of topics and a large number of participants, and is the main channel for Internet users to obtain information. "People’s Daily" is the media with high influence on social hot events in the wave microblog, from the opening day of the 2020 Tokyo Olympic Games to the end of the closing ceremony, among all the Olympic Games-related topics released by People’s Daily, there were 343 topics with more than 50,000 likes, and 343 topics were used as hot topics for research. Among the 343 hot topics, 64 were table tennis-related topics, and table tennis was the sport with the highest attention among the hot topics. The social network method was used to quantify the People’s Daily hot topics, establish a 2-mode network, study social actors as well as social structure from the perspective of relationships, and explain the structure of the 2-mode network and the influence of the macro-level structure on actors.